HLA-DR/DQ haplotype in rheumatoid arthritis: novel allelic associations in UK Caucasians. - Milicic, A; Lee, D; Brown, M; Darke, C; Wordsworth, B (2002)
OBJECTIVE: To elucidate the relative importance of the HLA-DR and HLA-DQ loci in conferring genetic predisposition to rheumatoid arthritis (RA). METHODS: HLA-DRB1 and HLA-DQB1 alleles were typed in a set of 685 patients with RA using sequence-specific polymerase chain reaction. Allele and phenotype frequencies were compared with those in 2 large sets of historical, ethnically matched healthy controls, using the relative predispositional effect method. RESULTS: Positive association was confirmed with the shared epitope positive HLA-DRB1 alleles associated with RA in Caucasians. A significant susceptibility effect was observed with HLA-DRB1*09, described in other ethnically diverse populations but not in Caucasians. A significant underrepresentation of the HLA-DRB1*0103 variant was noted among the RA cases, supporting the proposed protective role of the DERAA motif at residues 70-74 of the DRbeta molecule. No HLA-DRB1 independent association of the HLA-DQB1 alleles, implicated in predisposing to RA, was evident. CONCLUSION: These data corroborate the shared epitope hypothesis of susceptibility to RA and provide strong evidence for the DRB1 locus as the primary RA susceptibility factor in the HLA region.